EFFECT OF SEAWEED EXTRACT (ACADIAN) ON SOME FLOWERING CHARARCTRESTICS FOR TWO CULTIVARS OF SUMMER SQUASH Cucurbita pepo L. - Fathel Alhadede; Kabas Abdula (Mesopotamia Journal of Agriculture)
This experiment carried out at vegetables field of Horticulture and landscape department. College of Agriculture and Forestry. University of Mosul during the spring season (2018). The experiment included two factors. First was two hybrids of summer squash (MARVEL F1) and (ISMALIA F1), the second factor was included the seaweed extract (Acadian) at three concentrations of (0 , 2 and 4 gm.L-1). thus the experiment included 6 treatments (2 × 3). The experiment carried out in the field using split-plots system in R.C.B.D design the hybrids placed in the main plots while the sub plots included Acadian extract levels each treatment repeated three times. Analysis of variance and Duncan's multiple range test at 0.05 were applied for all recorded data. The results could be summarized as follows: Marvel and Ismailia hybrid plants did not differ in all studied flowering growth characteristics (appearance date of the first male and female flower (day) on the plant, number of male and female flowers     (flower.plant -1), sexual ratio, set ratio of female flowers).  The Acadian extract factor in both hybrids used showed it as the important and influencing factor in some studied traits, as its use led to significant results in some traits of flowering growth, and the treatments of Acadian extract at 2 and 4 g. L -1concentration did not differed between them significantly in most of the effects.